A sizing approach for optimizations of cascode low-noise amplifier with inductive source degeneration - Bao, Hongyu (Nanyang Technological University, 2024)
This thesis illustrates a single-ended cascode low-noise amplifier (LNA) topology with inductive source degeneration, which achieves dual-band coverage through a switchable output impedance matching network. The study focuses on theoretical analysis of critical performances of the LNA including the gain, noise performance and linearity, and an optimized LNA design is then proposed based on the analysis.